Diagnostic ACCURACY of SERUM β-Hcg in Threatened Miscarriages Keeping Ultrasound as Gold Standard - Safia Jan, Shahida Karamat, Parveen Azam, Palwasha Nasrullah, Qaiser Javed, Shafaq Mahmood, Jamshed Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Miscarriage is very common, with nearly one in four women experiencing an early pregnancy loss in her lifetime, although the majority of these are miscarried before they are recognized. 80% of miscarriages occur before 12 weeks of gestation, with miscarriage rates decreasing sharply after the first trimester. Miscarriage is the most common complication of pregnancy. About 25-30% of all pregnancies have some bleeding during the pregnancy. Usually no significant pain exists, although mild cramps may occur. More severe cramps may lead to an inevitable abortion. Objective: To determine the diagnostic accuracy of serum β-HCG in threatened miscarriages for early pregnancy loss keeping the ultrasonography as gold standard. Study Design: Cross Sectional validation study. Material and Methods: We conducted a cross-sectional validation study of 140 out/in patient with early pregnancy loss due to threatened miscarriages visiting to Pakistan Institute of Medical Sciences that is a tertiary care hospital from March 2022 to Feb 2023. Patients fulfilling the inclusion criteria were included in the study. Transabdominal/ Transvaginal ultrasound was performed to confirm the number and viability of pregnancy. At the same time measurement of serum β-HCG was done. The mean age of study patients was 30.12+15.08 years ranging from 15-45 years. Results: In our study 140 women presenting with thre60atened abortion were enrolled. 90]= , / [p-= [-p,.,.m-0p0b bnhju89hj bht67uy76tfrcv (64.2%) women had age less than 30 years while 50 (35.0. 8%) women had age more than 30 years. Regarding pregnancy related outcome 42(30%) females had miscarriage while 98 (70%) females continued normal pregnancy. 32 women had true positive (p=0.0032) and 10 women had false positive, (p=0.0004). 88 women had true negative (p=0.0005) and 10 women had false negative (p=0.0004). The sensitivity of serum β-HCG is 76.2%, (p=0.0003) with specificity of 89.8% (p=0.0005). The negative predictive value of β-HCG 89.7% (p=0.00032) and its positive predictive value is 76.2% (p=0.0005). Conclusion: In our study we found out that serum Beta-hCG has lower sensitivity and positive predictive value, while specificity, negative predictive value are towards higher. So this test has high validity as for as concerning the diagnosis of early pregnancy loss in Threatened miscarriage. Keywords: Threatened miscarriages, serumβ-HCG, Pregnancy loss, ultrasonography.